PENERAPAN MESIN SPINNER BERBASIS INVERTER UNTUK MENINGKATKAN PRODUKTIVITAS DAN KUALITAS KACANG METE PADA UMKM DININAS - Triyanna Widiyaningtyas; Soraya Norma Mustika; Yogi Dwi Mahandi; Muhammad Iqbal Akbar; Sujito Sujito; Moh Zainul Falah (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Cashew nuts are the fruit of the cashew plant, the most important of which is the cashew nut itself. Cashews are one of the most traded nut products. One of the MSMEs located in Singosari, Malang Regency is an MSME engaged in processed food products, namely cashew nuts. This MSME is called Dininas. This business was initiated by Mrs. Dini Mei Nastiti and has been established since 2018. Mrs. Dini's business produces around 10 – 50 kg per day with production in the form of cashew nuts. The problem faced by partners is the slicing process which still uses the conventional method, namely draining naturally by placing it in a container covering it with oil-absorbing paper, and then aerating it. Therefore the solution that is relevant in community service is the application of Inverter-based Spinner machines are more optimal, hygienic, and efficient to increase the amount of production. It is hoped that this community service with the application of Inverter-based Spinner machines can help Dinias SMEs in producing cashew nuts and meet demands from consumers. In addition, this machine is also expected to increase the productivity, quantity, hygiene, and quality of cashew nuts as well as increase profits for business managers.